An incidental pulmonary amyloidoma detected during 18F-FDG PET/CT assessment of large vessel vasculitis - George Ashton, MBChB, BMedSci; Karan Bir Singh, MBBS SCHP; Max Yan, MBBS FRCPA; Monica A Rossleigh, MBBS (Hons), M.D., FRACP; Anthony M. Sammel, MBBS, PhD, FRACP; Ivan Ho Shon, BSc(Med), MBBS, FRACP, FAANMS, PhD (Radiology Case Reports)
A 78-year-old woman underwent an 18F-FDG PET/CT scan as part of the investigation for giant cell arteritis. This demonstrated active large vessel vasculitis along with a moderately metabolically active pulmonary nodule in the left upper lobe; the appearances of which were concerning for malignancy. Subsequent biopsy of the pulmonary nodule was consistent with an amyloidoma. The nodule remained metabolically stable and of a similar appearance on repeat imaging performed 3 years later.